Dephytinizing and probiotic potentials of saccharomyces cerevisiae (NCIM 3662) strain for amelioration of nutritional quality of functional foods - Kumar Raja Puppala; Kumar , V. Ravi; Khire, Jayant; Dharne, Mahesh (Probiotics and Antimicrobial Proteins, 2018)
Increase of undigested complexes of phytic acid in food is gaining serious attention to overcome nutritional challenges due to chelation effects. We investigated soil-borne yeast phytase from Saccharomyces cerevisiae (NCIM 3662) for dephytinization of foods, probiotic properties, and process development. The strain produced 45 IU/DCG by cell-bound phytase in an unoptimized medium was increased fourfold (164 IU/DCG) in 12 h using statistical media optimization. The process was scaled-up up to 10-L fermenter scale with increased phytase productivity of 6.4 IU/DCG/h as compared to the lab scale. The strain displayed probiotic characteristics like tolerance to artificial gastric acid conditions, hydrophobicity, autoaggregation, coaggregation, and bile salt hydrolase (BSH) activity. Further, it could dephytinize (removal of phytic acid; an anti-nutritional factor) functional foods like ragi (finger millet) flour, soya flour, chickpea flour, and poultry animal feed. A combination of cell-bound dephytinizing phytase and nutrition-ameliorating probiotic traits of S. cerevisiae (NCIM 3662) presents profound applications in food technology sector.

Evaluation of Candida tropicalis (NCIM 3321) extracellular phytase having plant growth promoting potential and process development - Puppala, Kumar Raja; Naik, Tejali; Shaik, Alfina; Dastager, Syed; Kumar, V. Ravi; Khire, Jayant; Dharne, Mahesh (Biocatalysis and Agricultural Biotechnology, 2018)
Phytase is known to provide a solution for depletion of phosphorus (P). It helps it by hydrolyzing the insoluble P source in soil which is phytate. In this study, provides insight on yeast Candida tropicalis (NCIM 3321) which produces cell bound and extracellular thermostable phytase. The media components were optimized to enhance the enzyme production and checked for plant growth promoting activity. On optimization the isolate exhibited enhanced cell bound and extracellular phytase activity by four folds (from 236 to 1024 IU DCG⁻¹) and by five folds (from 0.46 to 1.95 IU ml⁻¹) respectively in 36 h. The production time decreased to 24 h compare to shake flask on Up-scaling the production process upto 10 L scale, thus increasing the productivity of cell bound (1810 IU DCG⁻¹day⁻¹) and extracellular phytase (6.08 IU ml⁻¹ day⁻¹). The crude phytase (12 IU) from NCIM 3321 strain was studied for plant growth promotion activity in lab scale and field level experiments with maize crop. Findings of the study revealed that the extracellular phytase derived from non pathogenic C. tropicalis (NCIM 3321) was found to be plant growth stimulating by increasing the available P in soil. Our findings of phytase isolated from non-pathogenic yeast C. tropicalis NCIM 3321 exhibited dephytinization potential. Therefore, current study may have profound application in sustainable agriculture.